The Influence of Tourist Attraction, Accessibility, and Facilities on the Decision to Visit the Gajah Mungkur Wonogiri Reservoir Tourist Attraction - Rully, Aviando; Darsono, Darsono; Widodo, Zandra Dwanita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
A destination or region with many factors taken into consideration. This research aims to determine the influence of (1) tourist attractions, (2) accessibility, and (3) facilities on visiting decisions, either partially or simultaneously. This research uses a quantitative research method with an instrument in the form of a questionnaire distributed to people who have visited the Gajah Mungkur Wonogiri Reservoir tourist attraction. This research was conducted at the Gajah Mungkur Reservoir Wonogiri tourist attraction. The time this research was conducted was 10 November 2024 - 31 January 2025. This research used primary data and secondary data. The population in this study are people who have visited the Gajah Mungkur Wonogiri Reservoir tourist attraction, including all subjects who have characteristics according to the research focus. Samples were taken using an accidental sampling technique. The minimum number of respondents required in this research is 100 people. To test the quality of the data, validity and reliability tests were carried out. Data analysis was carried out using the classic assumption test, multiple linear regression test, and hypothesis testing. The research results show that tourist attractions partially influence the decision to visit by 29.8%. Accessibility has an impact of 15.3%, and Facilities has an impact of 60.2%. Simultaneously these three variables have a significant impact on Visiting Decisions, with a significance value of 0.000 < 0.05. The coefficient of determination obtained shows that 67.7% of the variation in Visiting Decisions can be explained by Tourist Attraction, Accessibility and Facilities, while 32.2% is explained by other variables not studied